Acidic oral environment’s potential contribution to palladium-induced systemic contact dermatitis: Case report - Takeya Adachi, MD, PhD; Katsunori Masaki, MD, PhD; Kazuyo Sujino, MD; Utako Okata-Karigane, MD; Taro Murakami, MD; Chiaki Takahashi, MD; Shiori Nakayama, DMD; Saki Tomiyasu, MD; Masato Asaoka, MD; Hiroki Kabata, MD, PhD; Jun Miyata, MD, PhD; Hayato Takahashi, MD, PhD; et al. (Journal of Allergy and Clinical Immunology: Global, 2024)
Acidic oral environments may trigger systemic contact dermatitis via ionization of metals, including palladium. A patch test revealed a late delayed positive response to palladium, emphasizing the need for nuanced diagnostic approaches for allergy management.